Babylonian features in Iraqi fashion fabric designs (Journal of the College of Basic Education, 2022)
The Babylonian costumes were affected by the ancient civilizations in the region as Tigris and Euphrates both were a crossing road for the armies. Its feature was concentrated on the Babylonian feature.For example the Hebrew fashion was closer to the Assyrian fashion which covers all the body.If we speak about human stories, we find that the first man was covering his body with the thing closer to his hand. Animal hide was used until the days of Noah (a.s.). The various crafts began to appear. The trinkets and the wool textile began to emerge. In the light of this, the researcher pointed out the problem of the study by posing the following questions:Do the feature of the Babylonian civilization have s role in the Iraqi fashion design?The aim of the study was the following:To know the elements and symbols derived from the Iraqi heritage.Stating the aesthetic and expressive features of the Iraqi fashion design.The researcher used the men and women costume to be studies and came up to the following:The samples used the Babylonian symbols inspired from their civilization (Ishtar Gate) through distribution their items to the men and women fashion.Through the analysis of the sample models,, it appeared that the natural materials and synthesis ones were used which were analyzed.The findings of study are:The designs of men and women fashion depended on the Babylonian symbols in their design constituent.The elements and features have played an effected a role in design. The results show the effectiveness of the colors as formal space treatments which reflected the appearance features of the design constituent.